2013
DOI: 10.1136/bmjopen-2013-003733
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional and national sodium intakes in 1990 and 2010: a systematic analysis of 24 h urinary sodium excretion and dietary surveys worldwide

Abstract: ObjectivesTo estimate global, regional (21 regions) and national (187 countries) sodium intakes in adults in 1990 and 2010.DesignBayesian hierarchical modelling using all identifiable primary sources.Data sources and eligibilityWe searched and obtained published and unpublished data from 142 surveys of 24 h urinary sodium and 103 of dietary sodium conducted between 1980 and 2010 across 66 countries. Dietary estimates were converted to urine equivalents based on 79 pairs of dual measurements.Modelling methodsBa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
688
6
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 806 publications
(740 citation statements)
references
References 30 publications
30
688
6
16
Order By: Relevance
“…The results of the diet survey showed that the average amount of salt consumed in the surveyed households was less than what was reported in previous studies (de Brito-Ashurst et al 2009;Powles et al 2013). As the level of salinity in the drinking water also was not high, the overall situation in the study area did not seem to be that serious.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…The results of the diet survey showed that the average amount of salt consumed in the surveyed households was less than what was reported in previous studies (de Brito-Ashurst et al 2009;Powles et al 2013). As the level of salinity in the drinking water also was not high, the overall situation in the study area did not seem to be that serious.…”
Section: Discussionmentioning
confidence: 39%
“…Even if people could only get water with sodium levels as high as 374.3-817.0 mg/L-equivalent to salt intakes of 1.90-4.15 g/day, assuming an intake of 2 L of water per daythe current level of salinity in drinking water in the coastal zones of Bangladesh would still be acceptable to the human body considering people in the central Asian countries Fig. 9 Spatial distribution of salt intake in the study area in Chakaria Upazila, Bangladesh, 12 February-13 May 2016 consume 14.01 g of salt per day (Powles et al 2013), while the average salt intake by diet in Bangladesh is 9-10 g/day. But it will take time for the human body to adapt to this kind of change, and it is uncertain how sudden the environmental change is.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42 Saltinntaka á Íslandi hefur þó staðið nokkurn veginn í stað á árabilinu 1990 til 2010 en er samt sem áður um það bil 9 g/dag að meðaltali, sem jafngildir 3,6 g/dag af natríum og er naestum tvöfalt það magn sem WHO maelir með. 42 Það er því ólíklegt að breyting á saltinntöku skýri ein og sér fyrrnefnda laekkun í meðaltali blóðþrýstings hér á landi. Líklega vega aðrir þaettir þyngra.…”
Section: Tóbaksreykingarunclassified